The effect of ESG, inventory intensity and managerial ownership on tax avoidance - Ramadhan, Luthfi; Wadi, Indra (WIM Solusi Prima, 2024)
This study aims to determine the influence of ESG (Environment, Social, And Governance), Inventory Intesity, and Managerial Ownership on Tax Avoidance. Tax Avoidance is a dependent variable and ESG (Environment, Social, And Governance), Inventory Intesity and Managerial Ownership are independent variables This type of research is carried out using a quantitative method and the sampling technique is purposive sampling. The population in this study is all companies listed on the Kompas100 stock index and the Indonesia Stock Exchange during the 2018-2022 period. The number of companies used as a research sample is 10 companies. The analysis method uses multiple regression analysis, T test and F test using Eviews 12. The results showed that the influence of ESG (Environment, Social, And Governance) had no effect on Tax Avoidance, Inventory Intesity had an effect on Tax Avoidance and Managerial Ownership had an effect on Tax Avoidance. Meanwhile, ESG (Environment, Social, And Governance), Inventory Intesity, and Managerial Ownership have a simultaneous effect on Tax Avoidance. This research is useful in providing this information to help the Directorate General of Taxes increase corporate income tax collection by companies, as well as direct company policies to comply with tax laws and avoid irregularities. For the authors, this information adds insight into ESG, inventory intensity, and tax accounting to reduce tax avoidance practices.